Hubungan Iklim Kerja dan Teknologi Pembelajaran dengan Kualitas Pembelajaran Geografi pada SMA Negeri di Palangka Raya - Sutya Devi; Teguh Pribadi; Elyta Vivi Yanti; Sriyana Sriyana (Anterior Jurnal, 2019)
Teachers are an essential component of education as well a determinant of the quality of education. The Teacher’s professionalism is characterized by improving the learning quality (LQ) through the utilization and optimization of learning technology. Also, the quality of teaching is also supported by a conducive working environment conditions at the school. This study reported the results of research which investigated the correlation between school climate (SC) and learning technology utilization (LTU) with LQ. Sixteen participants from geographic subject teachers at the State Senior High School (PSHS) in Palangka Raya have responded to the questionnaire and recorded their perceptions of SC, LTU, and LQ. Spearman correlation analysis was used to test their correlation. This study revealed a positive relationship between LTU and LQ. As for the SC did not give influence on the LQ at PSHS in Palangka Raya. So that improving the LQ can be done by enhancing the ability of teachers in LTU and use it in teaching and learning activities in the classroom.